2004
DOI: 10.1074/jbc.m306576200
|View full text |Cite
|
Sign up to set email alerts
|

ART-27, an Androgen Receptor Coactivator Regulated in Prostate Development and Cancer

Abstract: Androgen receptor trapped clone-27 (ART-27) is a newly described transcriptional coactivator that binds to the N terminus of the androgen receptor (AR). Given the vital importance of AR signaling in prostate growth and differentiation, we investigated the role of ART-27 in these processes. Immunohistochemical studies indicate that ART-27 protein is expressed in differentiated epithelial cells of adult human prostate and breast tissue. In prostate, ART-27 is abundant in AR-positive prostate luminal epithelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 43 publications
(39 reference statements)
3
39
1
3
Order By: Relevance
“…In vivo staining showed that URI, Art-27, and AR were expressed in prostate epithelial cells (Fig. 5d), with only negligible URI and Art-27 expression in the stroma, as previously reported (23). These observations indicate that AR, URI, and the AR cofactor Art-27 are colocalized in prostate epithelial cells.…”
Section: Uri Represses Ar-mediated Gene Transcription It Has Beensupporting
confidence: 65%
“…In vivo staining showed that URI, Art-27, and AR were expressed in prostate epithelial cells (Fig. 5d), with only negligible URI and Art-27 expression in the stroma, as previously reported (23). These observations indicate that AR, URI, and the AR cofactor Art-27 are colocalized in prostate epithelial cells.…”
Section: Uri Represses Ar-mediated Gene Transcription It Has Beensupporting
confidence: 65%
“…This once considered "ubiquitously expressed transcript" is actually tightly regulated both in a cell line-and developmental stage-specific fashion and is downregulated in prostate cancer cells, consistent with a role as an inhibitor of androgen-mediated cellular proliferation (Taneja et al 2004;Nwachukwu et al 2007). In a separate study, UXT was also shown to bind the transcriptional repressor Evi1 and inhibit its cell transformation property in Rat1 cells (McGilvray et al 2007).…”
Section: Uxt (Art-27/stap1)mentioning
confidence: 76%
“…Consistent with these results, proliferation of LNCaP cells and colony formation were inhibited after overexpression of ARA70, thus suggesting its role as a tumour suppressor. There is also evidence that expression levels of the coactivator AR trapped clone-27 (ART-27) are substantially decreased in prostate cancer tissues (Taneja et al 2004).…”
Section: Ar Coactivator Alterations Occur In Endocrine Therapy-resistmentioning
confidence: 99%